Differential expression of CD44 variants among meningioma subtypes. Issue 3 (June 1996) - Suzuki, S O; Iwaki, T; Kitamoto, T; Mizoguchi, M; Fukui, M; Tateishi, J
Abstract : Aims/background —CD44 is a widely distributed cell surface molecule which has numerous isoforms generated by alternative splicing. The diverse functions related to the CD44 variants (CD44v) have been reported in various physiological and pathological conditions. The pattern of expression of CD44v among meningioma subtypes was investigated to ascertain whether CD44 variants play a role in a variety of biological processes, such as epithelial differentiation and extracranial metastasis. Methods —Twenty three meningiomas were studied immunohistochemically using novel antibodies directed against CD44 isoforms. Six of the 23 samples were analysed by reverse transcription polymerase chain reaction (RT-PCR), followed by Southern blotting with CD44v specific probes. Results —In meningothelial, fibrous and anaplastic meningiomas, a standard form of CD44 was detected by RT-PCR and was homogeneously expressed in tumour cells when studied immunohistochemically. CD44v was not detected in these subtypes. In secretory meningiomas, however, CD44v isoforms were strongly expressed in the cell clusters that produce secretory granules and also accumulated in the granules. The population of tumour cells immunopositive for CD44v was similar to that which stained with antibodies directed against carcinoembryonic antigen, epithelial membrane antigen and ezrin. On RT-PCR with Southern blotting, only the secretory type showed high level expression of CD44v. Conclusions —CD44v in meningiomas is expressed in relation to tumour cell differentiation towards the epithelial type.